The Family Socialization Methods (Democratic Style - Authoritarian Style ) and its relation with Family Adjustment A field study in secondary schools in the Damascus city. - Daod, Lila; Albalkhi, Mona (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The current research aims at identifying the relationship between the socialization methods of Family and family Adjustment among secondary school students. The study depends on the descriptive analytical. The scale used was socialization methods of Family and family Adjustment scale which has been distributed to a population of (94) male and female students. The results of the research show a weak correlation between family socialization methods and family Adjustment. The research also showed that there are statistically significant differences between males and females in the family Adjustment scale and this differences were high for females. There were statistically significant differences between the literary and the scientific competence students in the family Adjustment scale and these difference were high for literary students. The research offered some suggestion based on its results.